28th International Symposium on Automation and Robotics in Construction (ISARC 2011) 2011
DOI: 10.22260/isarc2011/0063
|View full text |Cite
|
Sign up to set email alerts
|

Representation Requirements of As-Is Building Information Models Generated from Laser Scanned Point Cloud Data

Abstract: Obtaining and utilizing as-is information with 3D imaging technologies, such as laser scanners, during various phases of facility life-cycle is becoming common practice. Both during construction and facility operations information derived from laser scanner data can serve many purposes by providing accurate information about the conditions of the facilities at the time of the scanning. Currently, the information derived from point clouds is typically represented as building information models (BIMs). Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Papers with regard to organizational/legal issues concentrate on collaboration of consortia partners in new building projects and in facility management (FM). Publications with a broader scope considering more than one of the previous issues [6,68,69] (e.g. LoD in BIM) and covering several BIM issues [7,8,17,27] mainly for new buildings are sporadic.…”
Section: Originalitymentioning
confidence: 99%
“…Papers with regard to organizational/legal issues concentrate on collaboration of consortia partners in new building projects and in facility management (FM). Publications with a broader scope considering more than one of the previous issues [6,68,69] (e.g. LoD in BIM) and covering several BIM issues [7,8,17,27] mainly for new buildings are sporadic.…”
Section: Originalitymentioning
confidence: 99%
“…Anil et al [10] identified several characteristics induced by the use of laser scanner data for as-is BIM creation. First of all, the point cloud density, which describes the average spacing between points, conditions the size of the smallest object that can be modelled.…”
Section: From Point Clouds To Building Information Modelmentioning
confidence: 99%
“…The first is used to describe the shape of an object, by means of an analytical, mathematical and abstract model. The second produces very dense and elaborate coordinate data points for the surfaces of a physical object [30,31]. For this reason, one objective of this paper is to perform an analysis of the accuracy of the EM, in two modes of data capture: (1) Photogrammetry to get 3D point coordinates; and (2) Photomodeling to get 3D point cloud and the color of the object observed.…”
Section: Introductionmentioning
confidence: 99%